Acceleration of Load Changes by Controlling the Operating Parameters in CFB Co-Combustion - Peters, Jens; Langner, Eric; Ströhle, Jochen; Epple, Bernd (Frontiers in Energy Research, 2021)
The integration of intermittent renewable energy sources into the electricity market requires flexible and efficient technologies that compensate for the fluctuating electricity demand. A circulating fluidized bed (CFB) boiler is a suitable solution due to its fuel flexibility, but the thermal inertia of the fluidized bed can have negative effects on the load following capabilities. This study investigates the influence of the operating parameters of the fire side on the speed of load changes on the waterside. Co-combustion of lignite, straw, and refuse derived fuel (RDF) was carried out. In a 1 MWth pilot CFB combustor fifteen load changes were performed with a varying step input of the primary air, the secondary air, and the fuel mass flow. The step input of the primary air had a large influence on the load ramps, as it strongly affects the solids concentration in the upper furnace. The step size of the fuel mass flow had a positive effect on the load change rate. Based on the results, concepts were developed to accelerate load ramping by controlling the hydrodynamic conditions and the temperature on the fireside.